Estudo da influência de aditivos de carbono sobre as propriedades eletroquímicas e morfologia do material ativo negativo de baterias chumbo-ácido - Carvalho, Cynthia Mayara de (2024)
In the current scenario of global warming, it is urgent to search for and use new energy sources that are renewable, low-cost, more energy-efficient and generate fewer greenhouse gases. In this context, there is a growing interest in energy accumulators and, among these, lead-acid batteries stand out, mainly because they are a consolidated, efficient and low-cost technology. In order to reduce greenhouse gas emissions, there is a growing industrial demand for electric and hybrid vehicles, which use "start-stop" technology and "regenerative brakes", which require the battery to work in partial state of charge mode, which causes sulfation, especially in the negative electrodes of lead-acid batteries, reducing their life cycle. Carbon-based additives applied to the negative electrode of the lead-acid battery slow down the sulfation process and increase the life cycle of the battery in a partial state of charge. Carbonaceous materials derived from biomass (biochar) have been used in electrochemical cell electrodes, as well as in capacitors and supercapacitors and have shown enormous potential to improve their physical and electrochemical properties compared to other carbonaceous materials, however, few studies with biochars have been performed on the negative electrodes of lead-acid batteries. Thus, the present work sought to bring contributions to the study of the influences of biochar on the physical and electrochemical properties of negative electrodes of lead-acid batteries. For this purpose, negative electrodes were made without additive (SA), with carbon black (NF) and biochar (BIO 700) additives, derived from eucalyptus bark biomass, at concentrations of 0.5, 1, 2 and 3% in relation to the mass of PbO used in the preparation of the electrode paste, which was composed of PbO, H2O and carbon, no added sulfuric acid. These electrodes were characterized by N2 adsorption, scanning electron microscopy (SEM), charge, discharge tests and capacity measurements. The results showed that the material containing biochar was superior to NF and SA in the charge, discharge and capacity tests. The biochar concentration with the highest reference capacity was 2% (210 mAg-1), concentration in which the ratio between the internal and external specific surface areas was 50%. It has been proven that biochar has become part of the internal structure of the precursor and active material. This effect decreased the BET surface area of the biochar-containing materials compared to those prepared without additive and with NF, however, it increased the electrochemical performance of the negative electrode. The specific capacity values (C20) obtained for the concentrations of 2% NF, 1% BIO 700 and 2% BIO 700 were higher or close to the C20 values obtained for negative electrodes, found in the literature, with a composition of sulfuric acid and other additives, in addition to carbon, in their paste. Thus, the physical and electrochemical superiority of biochar as an additive in the negative plate compared to NF, widely used in industries as an additive, was proven. This superiority was a consequence of the greater diversity of particle size, the greater diversity between basic and acid functional groups, the smaller external specific surface area, and the introduction of biochar to the bulk of the precursor and negative active material, demonstrating a better affinity of this carbon in relation to the NF. It is noteworthy that more studies should be carried out with biochars as additives to the negative plate of lead-acid batteries, in view of their better physical and electrochemical performance in relation to NF, so that more variables of this performance improvement are evidenced and controlled.